PENGARUH DIGITAL LEADERSHIP DAN WORK ENGAGEMENT PADA INNOVATION WORK BEHAVIOUR PADA GEN Z JAWA TENGAH - Chandra Sari, Kartika Dwi; Jaya, Yadi Fakhruzein Terang; Salsabela, Riska nadiya (UNPERBA, 2024)
This study aims to asses the relationship between Innovation Work Behavior with Digital Leadership and Work Engagement. The method to select the responden using purposive sampling, and it was conducted on 80 people Gen Z in Jawa Tengah. Further, the study using SEM-PLS with WrapPLS ver 7.0. The result support that Digital Leadership has a positif significant relationship with Innovative Work Behavior and Work Engagement. But, the findings found that the work engagement gen Z in Jawa Tengah didn’t affected Innovative Work Behavior. Gen Z in Indonesia has a realistic trait to face the work life, and the gen Z generally have a low rate of work engagement, but they have an innovative character. It is indicated that gen Z in Jawa Tengah probably didn’t need engage with the work to show innovative behaviour in organization